Unanticipated deals and acquirer returns: Evidence from Finland - Valli, Joonas (My University, 2022)
M&A activity seems to be an ever-increasing feature of the corporate landscape. In fact, the value of US M&A deals has risen from $45.5 billion in 1988 to $469.7 billion in 2017. However, this trend seems to be in stark contrast to the empirical implications of previous literature, which have time and again pointed out that M&As lead to a systematic loss of shareholder value as calculated by the negative or near-zero CARs found in multiple previous papers. The paper by Tunyi (2021) provides new evidence that in fact, these lackluster acquirer returns reported by previous studies are a result of the markets revision of probabilities regarding the published deal characteristics of highly anticipated deal announcements. Consequently, Tunyi (2021) contributes to the literature by pointing out that acquirers with the lowest acquisition likelihood (unanticipated acquirers) earned the highest returns of all acquirer groups, suggesting that the market reaction is not merely a revision of prior probabilities, but rather a reaction to brand new information. Consistent with this story, Tunyi (2021) also finds that the acquirers with the highest acquisition likelihood (anticipated acquirers) earned the weakest returns of all acquirers, suggesting a linear relationship between acquisition likelihood and acquirer returns. This study re-examines the findings of Tunyi (2021) in the Finnish stock market in the period from 2010 to 2020 by performing an event study. To conceptualize the results of the event study, the returns were measured over six different categories: means for each event window (3-day mean, 5-day mean, and 7-day mean), and medians for each event window (3-day median, 5-day median, and 7-day median). The main findings of this study can be summarized in three main points. First, acquirers in the Finnish market earned mean CARs upon M&A announcements of 3.0%, 3.4% and 2.6% for the 3-day, 5-day, and 7-day event windows respectively. These findings suggest that acquirers in the Finnish market have been able to create shareholder value through acquisitions in the observed time period. Second, unanticipated acquirers outperformed other acquirers in three of the six utilized categories, and tied for the best returns in two of the six categories, suggesting that unanticipated acquirers performed better than other acquirers in most circumstances. Third, anticipated acquirers earned the lowest CARs in only one of the six utilized categories, suggesting that the relationship between acquisition likelihood and acquirer returns is not as straightforward as proposed by Tunyi (2021). The results of this study help shareholders of publicly listed companies to analyse short-term returns upon M&A announcements more holistically, and thus, gain a better picture how the market views e.g., inorganic growth strategies.

Yrityskauppavolyymit ovat olleet vuosikymmenten ajan kasvussa maailmanlaajuisesti. Muun muassa Yhdysvaltain yrityskauppojen yhteenlaskettu vuosittain arvo on noussut 45.5 miljardista dollarista vuonna 1988, 469.7 miljardiin dollariin vuonna 2017. Aiheesta tehty aikaisempi tieteellinen tutkimus on osoittanut useita kertoja, että pörssiin noteeratut yritykset, jotka ovat tehneet yritysostoja, ovat systemaattisesti tuhonneet osakkeidensa arvoa sen seurauksena. Tunyin (2021) tuore tutkimus osoittaa, että aikaisempien tutkimusten heikot osaketuotot yritysostoja tehneille pörssiyrityksille johtuvat nimenomaan ennalta odotettujen yrityskauppojen julkistuksista, joiden yhteydessä markkinat reagoivat pelkästään julkistuksen sisältämiin uusin yksityiskohtiin. Tunyi (2021) nostaa myös esiin, että yritykset, joilla on pienin todennäköisyys ostaa toinen yritys, ovat itseasiassa luoneet arvoa osakkeenomistajilleen yrityskauppojen avulla. Tämä on seurausta siitä, että tällöin markkinat reagoivat julkistuksen yhteydessä täysin uuteen informaatioon, eivätkä pelkästään yksityiskohtien tarkentumiseen kuten odotettujen yrityskauppojen julkistusten yhteydessä. Tämän lisäksi, Tunyin (2021) tutkimuksen tuloksista saadaan selville, että yritysostotodennäköisyydellä ja yritysostajan osakkeen tuottojen välillä vallitsee käänteinen lineaarinen riippuvuus. Tämän tutkimuksen tavoitteena oli tutkia Tunyin (2021) löydösten validiteettia Suomen osakemarkkinoilla vuosien 2010 ja 2020 välillä. Tutkimuksessa tehtiin tapahtumatutkimus, jonka tuloksia mitattiin kuudella eri kategorialla: keskiarvoilla kolmessa eri aikaikkunassa ja mediaaneilla kolmessa eri aikaikkunassa. Tämän tutkimuksen tärkeimmät tulokset voidaan tiivistää kolmeen osaan. Ensiksi löydettiin, että yritysostoja tehneiden pörssiyritysten osakekurssit olivat reagoineet Suomessa keskimäärin positiivisesti yritysostojen julkistuksen yhteydessä. Koko otoksen keskimääräiset kumulatiiviset epänormaalit osaketuotot olivat 3.0%, 3.4% ja 2.6% mitattuna kolmen, viiden ja seitsemän päivän aikaikkunoilla. Toisekseen tutkimuksessa löydettiin, että odottamattomat yritysostajat, tarjosivat osakkeenomistajilleen keskimäärin parempia tuottoja kuin muut yritysostajat. Tämän ryhmän osakkeiden kumulatiiviset epänormaalit tuotot olivat muita yritysostajia parempia 3/6 kategoriassa ja jaetulla ensimmäisellä sijalla 2/6 kategoriassa. Kolmanneksi tutkimuksessa löydettiin, että todennäköisimpien yritysostajien osakkeet tuottivat huonoimmat kumulatiiviset epänormaalit tuotot vain 1/6 kategoriassa, joka osoittaa, että riippuvuus yritysostotodennäköisyyden ja yritysostajan osakkeen tuottojen välillä ei ole yhtä selkeä kuin Tunyin (2021) tutkimus antaa ymmärtää. Tutkimuksen tulosten perusteella pörssiyritysten osakkeiden omistajat pystyvät arvioimaan yrityskauppojen julkistuksen yhteydessä tapahtuvaa markkinoiden reaktiota kokonaisvaltaisemmin sekä arvioida mm. pörssiyritysten yritysostostrategiota holistisemmin.
Keywords: acquisition; yrityskaupat; osakkeet; rahoitus; sijoitukset (talous); arvopaperimarkkinat; mergers; return; anticipation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance